MiR-191-5p alleviates microglial cell injury by targeting Map3k12 (mitogen-activated protein kinase kinase kinase 12) to inhibit the MAPK (mitogen-activated protein kinase) signaling pathway in Alzheimer’s disease: Running Title: Role of miR-191-5p in Alzheimer’s disease - Wenjun Wan (Taylor & Francis Group, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease. Multiple reports have elucidated that microRNAs are promising biomarkers for AD diagnosis and treatment. Herein, the effect of miR-191-5p on microglial cell injury and the underlying mechanism were explored. APP/PS1 transgenic mice were utilized to establish mouse model of AD. Amyloid-β protein 1-42 (Aβ1-42)-treated microglia were applied to establish in vitro cell model of AD. MiR-191-5p expression in hippocampus and microglia was measured by reverse transcription quantitative polymerase chain reaction. The viability and apoptosis of microglia were evaluated by Cell Counting Kit-8 assays and flow cytometry analyses, respectively. Binding relationship between miR-191-5p and its downstream target mitogen-activated protein kinase kinase kinase 12 (Map3k12) was determined by luciferase reporter assays. Pathological degeneration of hippocampus was tested using hematoxylin-eosin staining and Nissl staining. Aβ expression in hippocampus was examined via immunohistochemistry. In this study, miR-191-5p was downregulated in Aβ1-42-stimulated microglia and hippocampal tissues of APP/PS1 mice. MiR-191-5p overexpression facilitated cell viability and inhibited apoptosis rate of Aβ1-42-treated microglia. Mechanically, miR-191-5p targeted Map3k12 3ʹ-untranslated region to downregulate Map3k12 expression. MiR-191-5p inhibited Aβ1-42-induced microglial cell injury and inactivated the MAPK signaling by downregulating Map3k12. Overall, miR-191-5p alleviated Aβ1-42-induced microglia cell injury by targeting Map3k12 to inhibit the MAPK signaling pathway in microglia.